1989
DOI: 10.1177/104990918900600303
|View full text |Cite
|
Sign up to set email alerts
|

A specialized hospice for dementia patients and their families

Abstract: This article reports the development of a small pilot program and briefly describes its activities. The growing number of dementia patients in American communities indicates a need to extend hospice services to these patients and their families. It is difficult to determine at present whether this need could be met more effectively by encouraging existing hospices to accept these patients or by establishing specialized programs such as this one. Research in this area is indicated, as well as the sharing of inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Despite the fact that hospice care for people with dementia was described in US studies around 30 years ago [14, 15], this paper has made explicit the different perspectives on how to (further) develop services for people with the dementia in the last phase. Some belief that a cancer palliative care model equally applies to dementia [35], or wonder if end-of-life care is special at all although it seems more difficult to provide person-centred care if the person cannot express him- or herself well due to advanced dementia or perhaps superimposed acute illness [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that hospice care for people with dementia was described in US studies around 30 years ago [14, 15], this paper has made explicit the different perspectives on how to (further) develop services for people with the dementia in the last phase. Some belief that a cancer palliative care model equally applies to dementia [35], or wonder if end-of-life care is special at all although it seems more difficult to provide person-centred care if the person cannot express him- or herself well due to advanced dementia or perhaps superimposed acute illness [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been a dearth of literature on service development, apart from US initiatives in the 1980s [14, 15]. Because of the disappointing results of search strategies combining hospice/end of life/terminal care with dementia, we concluded that to learn more about service development and its facilitators and barriers, we needed to look for non-scientific reports, search for projects and health care services specialized in care for people with dementia in the terminal phase and consult with experts.…”
Section: Methodsmentioning
confidence: 99%
“…Maximal comfort rather than prolonged survival may be the preferred treatment for persons with late stage dementia. Although a hospice type approach for persons with late stage dementia has been advocated, few demonstration programs have been implemented to test the need for and efficacy of the hospice model in this population 15–17 . A major barrier to the use of hospice care by persons with advanced dementia is related to uncertainty about length of survival in a disease in which the major cause of death is intercurrent infection.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, survival is dependent on how aggressively these infections are treated. 17 Although life expectancy may be difficult to estimate, hospice care is the appropriate form of treatment for many persons with advanced dementia.v 9,15,17 Recently, both the Advisory Panel on Alzheimer's Disease and the Institute of Medicine have identified the need for more research on elderly populations in need, the cost effectiveness of programs, and the value place on program alternatives by patients and families. 18,19 In keeping with these research goals, we recommend that future research focus on the development and testing of cost-effective clinical interventions that promote quality of life and quality of care for late stage dementia patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…For many patients, particularly those with advanced dementia, a hospice approach may be appropriate and desirable 6 8 . The issue of resuscitation may assume less importance than the use of feeding tubes, hydration, or antibiotics.…”
mentioning
confidence: 99%